A New Alternative Synthesis of Salicylaldazine via Microwave Irradiation Method - Kassim K.; Hamali M.A.; Yamin B. (Hindawi Limited, 2024)
Two diazine Schiff base ligands, HLa and HLb, derived from thiocarbohydrazide and salicylaldehyde derivatives were synthesized using the microwave-assisted synthesis approach. The confirmation of both ligands was elucidated through physiochemical and spectroscopy techniques as well as single X-ray crystallography diffraction. The analyses showed that the ligands synthesized were formed as azine instead of thiocarbohydrazone based on the missing thione, C=S moiety, throughout FTIR and NMR spectrascopic data. This finding was further concluded by X-ray crystal analysis. The biological properties of these ligands were screened using the disc diffusion method. The result shows that HLb shows significant inhibition towards all of the bacteria tested.